Studies of the population structure and generic diversity of domesticated and "wild" ostriches (Struthio camelus) - Bezuidenhout, Cornelius Carlos (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2000)
DNA sequencing and restriction fragment length polymorphism analysis (RFLP) of polymerase chain reaction (PCR) amplified mitochondrial DNA fragments, and random amplified polymorphic DNA sequence (RAPD) analysis were techniques evaluated in this study for applicability in the investigation various aspects of genetic diversity within the ostrich (Struthio camelus). The genetic aspects that were investigated were (i) relationships between ostrich subspecies, (ii) genetic variability between and within domesticated populations of southern African ostriches (Struthio camelus australis), (iii) linking egg production in domesticated ostriches to RAPD profiles, and (iv) determining the zygosity of twin ostriches. In the first part of this study DNA sequencing and the polymerase chain reaction - restriction fragment length polymorphism (PCR-RFLP) methods were evaluated for resolving genetic differences in the small mtDNA fragments ofthe ostrich. DNA sequencing ofPCR amplified 450 bp 12S rRNA gene fragments of representatives from the southern African population ostrich (S.c. australis) did not reveal any differences between the populatiohs from different geographical areas, representing ostrich lineages with different breeding histories. The PCRRFLP analysis ofmtDNA fragments (450 bp 12S rRNA gene fragment and 550 bp D-loop region) also did not reveal any genetic variability between the domesticated s.,c. australis populations included in this study. PCR-RFLP analysis of a 450 bp 12S rRNA gene fragment, however, showed differences between the subspecies s.c. australis and s.c. molybdophanes. The proportion of shared fragments (F) between these two subspecies was 0.286 and nucleotide sequence divergence estimated at 8.9 %. Divergence time between these two subspecies was estimated at 4.5 million years ago. The data presented from this study are comparable to the data from a previous study in which the entire mitochondrial genome and a larger number of restriction enzymes were used. The PCR-RFLP method thus demonstrated its usefulness for genetic studies of ostriches at thesubspecies level. The sequences used in this study could not reveal any markers that were useful for genetic studies of ostriches at the population level. In the second part of the study the RAPD method was evaluated for application in the genetic studies of ostriches. RAPD profiles, based on three RAPD primers, revealed differences between three subspecies of ostriches and indicated relationships between these subspecies that are consistent with observations from other studies. The numerical analysis of pooled and individual primer data demonstrated that the subspecies s.c. australis is more closely related to s.c. massaicus than to s.c. molybdophanes. RAPD marker differences between s.c. molybdophanes on the one hand, and s.c. massaicus and s.c. australis on the other is also consistent with observations from studies that proposed separate specie~ status for s.c. molybdophanes. RAPD analysis by five primers revealed geographic variation between s.c. australis populations. The clustering patterns observed in the dendrograms and Neighbour Joining Trees generated by computer programs showed trends of separating ostric1;t populations into geographical groups, possibly reflecting their different breeding histories. In the RAPD profiles of the inbred population, band-sharing was generally greater than in the outbreeding group. RAPD analysis thus showed that it may be a useful method in the population studies of domesticated S. c. australis. RAPDs also generated data that grouped ostriches according to trends in egg production capabilities. Analysis ofRAPD profiles by computer software showed a Neighbour Joining Tree and a dendrogram that predominantly grouped ostriches into clusters associated with either good or poor egg production. Evidence supporting the suitability of RAPDs as a tool in breeding programmes of ostriches was thus provided by this study. RAPDs also provided data, demonstrating that two sets of ostrich twins were non-identical twins. It was demonstrated by this study that RAPDs analysis may be a useful technique for applying to (1) systematic (2) population (3) breeding and (4) twin studies of ostriches (Struthio camelus).
Keywords: Ostriches; Ostriches -- Genetics; Ostriches -- South Africa